Analisis Retorika Dakwah Digital Umi Lailatur Rohmah Hadi dalam Perspektif Aristoteles dan Kenneth Burke - Maharani, Silky Sabella (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2023)
This study examines the communication strategies used by Umi Lailatur Rohmah Hadi, a young preacher from Surabaya, with a focus on classical and modern rhetorical analysis. Aristotle's classical rhetorical approach, namely ethos (credibility), pathos (emotion), and logos (logic), is combined with Kenneth Burke's modern rhetorical theory, dramatism (analysis of communication as drama) to understand the effectiveness of message delivery. The results of the analysis show that Umi Lailatur is able to combine personal credibility, a touching emotional approach, and logical arguments that are easy to understand, thus building a strong affinity with audiences from various backgrounds. The simple narrative style and the insertion of salawat and songs are also characteristics that strengthen the appeal of her communication. Keywords : Retorika Dakwah, Umi Lailatur, Ethos, Pathos, Logos, Dramatisme